Extrapulmonary Tuberculosis in Denmark From 2009 to 2014; Characteristics and Predictors for Treatment Outcome. (3rd September 2019) - Holden, Inge K; Lillebaek, Troels; Andersen, Peter H; Bjerrum, Stephanie; Wejse, Christian; Johansen, Isik S
Abstract: Background: Extrapulmonary tuberculosis (EPTB) represents an increasing percentage of tuberculosis (TB) cases in Europe. However, strategies on TB prevention and successful treatment outcomes primarily target pulmonary TB. In this nationwide study, we present characteristics of EPTB, treatment outcomes, and predictors for unfavorable treatment outcomes. Methods: All patients diagnosed with EPTB from 2009 to 2014 were included. Logistic regression analyses were used to identify risk factors for unfavorable outcome. The following definitions were used: unfavorable outcome: the sum of treatment failed, lost to follow-up, and not evaluated; patient delay: time from TB-related symptom onset until first hospital contact related to TB; doctor delay: time from first TB-related contact in the health care system to start of TB treatment. Results: A total of 450 EPTB cases were notified, which represented 21.1% of all TB cases in Denmark. Immigrants accounted for 82.9%. Lymph nodes were the most common site of EPTB (55.4%) followed by pleural TB (13.4%). Patient delay was significantly longer among immigrants than Danes (60 vs 30 days; P < .01), whereas doctor delay was significantly longer among Danes (38.5 vs 28 days; P < .01). Treatment completion rates were high and reached 90.9% in 2014. Male gender (odds ratio [OR], 5.18; 95% confidence interval [CI], 1.79–15.04) and age 0–24 years (OR, 16.39; 95% CI, 2.02–132.64) were significantly associated with unfavorable outcome. Conclusions: EPTB represented a significant number of all TB cases and was predominantly seen among younger immigrants in Denmark. To maintain high treatment completion rates, increased focus on male gender and young age is needed.